1997
DOI: 10.1002/(sici)1097-4679(199706)53:4<319::aid-jclp4>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among child abuse, date abuse, and psychological problems

Abstract: Data on child abuse, date abuse and psychological problems were gathered from the same participants, 133 female undergraduates, in order to better examine possible relationships among the variables. Verbal abuse in childhood or on dates was examined as well as physical and sexual abuse. Factors influencing whether people remain in or leave abusive relationships were examined, along with possible mediators of the relationships between child abuse, date abuse, and psychological problems. Verbal, physical, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 0 publications
4
22
1
1
Order By: Relevance
“…Congruent findings were found in related studies (Hendy et al 2003;Noland et al 2004;Sappington et al 1997;Slashinski (Smith et al 2003), Schaaf and McCanne indicated that female college students who were physically abused in childhood reported higher rates of physical and sexual victimization in adulthood, compared to childhood sexual abuse victims (Schaaf and McCanne 1998). Such findings strongly supported ours.…”
Section: Discussionsupporting
confidence: 89%
“…Congruent findings were found in related studies (Hendy et al 2003;Noland et al 2004;Sappington et al 1997;Slashinski (Smith et al 2003), Schaaf and McCanne indicated that female college students who were physically abused in childhood reported higher rates of physical and sexual victimization in adulthood, compared to childhood sexual abuse victims (Schaaf and McCanne 1998). Such findings strongly supported ours.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this theory, empirical work has demonstrated that childhood physical abuse and interparental violence exposure are associated with anger-related dysregulation in children and adults (Cicchetti & Toth, 2005; Repetti et al, 2002; Sappington et al, 1997). For example, exposure to family violence has been shown to increase sensitivity to anger in children (Repetti et al, 2002).…”
mentioning
confidence: 84%
“…One form of emotion dysregulation associated with both a history of childhood family violence exposure and IPV victimization is anger-related dysregulation (Sappington, Pharr, Tunstall, & Rickert, 1997). Drawing on social learning theory (Bandura, 1973), anger-related dysregulation, or an inability to manage and express anger effectively, may be learned through the observation and imitation of others’ behaviors and through direct behavioral conditioning from parental figures.…”
mentioning
confidence: 99%
“…The majority of studies including CA and anger have focused on CA perpetration; however, one study found that both CSA and CPA victimization were positively associated with general anger and hostility among female undergraduates (Sappington et al 1997). A substantial body of literature has suggested a relationship between anger and IPV perpetration (Eckhardt et al 2002(Eckhardt et al , 2008Murphy et al 2007; for review, see Norlander and Eckhardt 2005).…”
Section: Interrelationships Between Ca Ptsd Anger and Ipv Perpetramentioning
confidence: 99%